Pharmaceutical Care in Ontario - Dzionek, Jacqueline (Journal of Medical Science, 2020)
Pharmaceutical care is an integral part of global healthcare. Indeed, pharmacists are recognised as a primary point of care, providing many services to optimise the patient’s healthcare. The article provides insight on how expanding the scope of pharmacists’ practice can facilitate collaboration between healthcare providers, relieve the workload of the physicians, also providing patients with optimal healthcare service globally. This article focuses specifically on the expanded scope of pharmacists in Ontario, Canada and the services that pharmacists can provide in the pharmacy for all patients.
Keywords: pharmacist; expanded scope of practice; services; medication management; prescribing; injections